Measurement of top quark polarization in tt¯ lepton+jets final states - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2017)
We present a measurement of top quark polarization in tt- pair production in pp- collisions at s=1.96 TeV using data corresponding to 9.7 fb-1 of integrated luminosity recorded with the D0 detector at the Fermilab Tevatron Collider. We consider final states containing a lepton and at least three jets. The polarization is measured through the distribution of lepton angles along three axes: the beam axis, the helicity axis, and the transverse axis normal to the tt- production plane. This is the first measurement of top quark polarization at the Tevatron using lepton+jet final states and the first measurement of the transverse polarization in tt- production. The observed distributions are consistent with standard model predictions of nearly no polarization.